Risk assessment of Islamic banking products: special focus on mudarabah and musharakah - Hassan, Rusni; Salman, Syed Ahmed; Haron, Razali; Yusoff, Adnan; Hassan, Aznan; Mohd Yusoff, Syarah Syahira (Pontificia Universidad Catolica de Chile, 2023)
The banking industry is widely regarded as one of the sectors vulnerable to the effects of hazardous trade. To shape the banking industry, many international organizations, such as the BASEL Committee on Bank Supervision and the IFSB (Islamic Financial Services Board), as well as many developed countries and developing countries, have implemented risk management guidelines. The liquidity risk, credit risk, operational risk, and market risk that banks are exposed to are the most significant risks. According to the researchers, all risks must be managed concurrently; otherwise, mitigating one risk might result in additional risk. The objective of this paper is to analyze the risks that are associated with the contracts that are being made available by the Islamic banking institutions. The article concentrates on the two Shariah contract types: Mudarabah and Musharakah. This paper has been written after an extensive review of the relevant past studies. The findings of this paper show that each transaction in Islamic banks possesses its own set of one-ofa-kind characteristics. Because of this, the contracts governing each transaction are also unique. Consequently, Islamic banks are exposed to more significant risks, including equity investment risk, return on equity risk, etc. Some contracts may be exposed to the same risks; however, how these risks affect each might be unique. All contracts, including those of Mudarabah and Musharakah, are sensitive to market, credit, liquidity, and operations risks. However, the approach that should be taken toward each contract is distinct. As a result, Islamic banks need an effective risk management method. This study provides bankers, investors, and regulators with new insights